2011
DOI: 10.3174/ajnr.a2841
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Assisted Coiling of Intracranial Bifurcation Aneurysms Leads to Immediate and Delayed Intracranial Vascular Angle Remodeling

Abstract: BACKGROUND AND PURPOSE:Wide-neck bifurcating aneurysms are increasingly treated with intracranial stent-assisted coiling by using shape-memory alloy microstents. We sought to investigate the short-and long-term effects of intracranial stent implantation on the geometry and angular conformation of the stent-coiled vascular bifurcation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 29 publications
5
90
1
Order By: Relevance
“…Intracranial stents have a multifactorial favorable role in aneurysm embolization: It may enable dense coil mass packing [16,17], change vascular morphology, induce intraaneurysmal flow modifications [18][19][20][21][22], and provide a structural basis for endothelialization [23,24]. However, the use of stent-assisted coil embolization more commonly has been reserved for unruptured aneurysms in order to determine the difference between thromboembolic events and hemorrhagic events when treating acutely ruptured aneurysms compared with unruptured ones.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial stents have a multifactorial favorable role in aneurysm embolization: It may enable dense coil mass packing [16,17], change vascular morphology, induce intraaneurysmal flow modifications [18][19][20][21][22], and provide a structural basis for endothelialization [23,24]. However, the use of stent-assisted coil embolization more commonly has been reserved for unruptured aneurysms in order to determine the difference between thromboembolic events and hemorrhagic events when treating acutely ruptured aneurysms compared with unruptured ones.…”
Section: Discussionmentioning
confidence: 99%
“…Stent-related changes in vascular geometry have been observed in the treatment of cerebral aneurysms. 3,5) Vascular geometry was changed by stent placement in anterior communicating artery aneurysms, and the angle of change ranged from 7.609to 74.889 , with a mean of 29.959 . 5) Change in vascular geometry also occurred after stent placement for bifurcation aneurysms, and the vascular angles changed by a mean of 189on immediate angiograms and 349on follow-up angiograms.…”
Section: Discussionmentioning
confidence: 99%
“…They observed increases of the radius of curvature of more than 50 % after stent implantation. Gao et al [2]. as well as Chau et al [7] reported that anatomical deformation is more likely in distal (middle cerebral and anterior communicating artery) than in proximal (e.g., internal carotid artery) locations.…”
Section: Introductionmentioning
confidence: 99%
“…The investigated unruptured aneurysm was located at the middle cerebral artery, where according to Gao et al [2] and Chau et al [7] anatomical deformations are more likely. Placement of a laser-cut stent (Acclino flex, Acandis GmbH & Co. KG, Pforzheim, Germany) for stent-assisted coiling led to a marked anatomical deformation of the parent and nearby arteries (Figure 1).…”
Section: Case Description and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation